2016
DOI: 10.1371/journal.pone.0161867
|View full text |Cite
|
Sign up to set email alerts
|

C5a Induces the Synthesis of IL-6 and TNF-α in Rat Glomerular Mesangial Cells through MAPK Signaling Pathways

Abstract: Inflammatory response has been reported to contribute to the renal lesions in rat Thy-1 nephritis (Thy-1N) as an animal model of human mesangioproliferative glomerulonephritis (MsPGN). Besides C5b-9 complex, C5a is also a potent pro-inflammatory mediator and correlated to severity of various nephritic diseases. However, the role of C5a in mediating pro-inflammatory cytokine production in rats with Thy-1N is poorly defined. In the present studies, the levels of C5a, interleukin-6 (IL-6) and tumor necrosis facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 46 publications
(43 reference statements)
2
21
0
1
Order By: Relevance
“…Moreover, the induction and maintenance of various pain conditions were activated by the ERK1/2 MAPK pathway. [2930] Recent work showed that the voltage-gated sodium channels, such as Nav1.3 and Nav1.8, can been regulated by MAPK pathway in DRG neurons and the voltage-gated sodium channels play important role in neuralgia. [3132] Consequently, we believe the migraine may be caused by cytokines, such as IL-6 and IL-1β which induced by CGRP.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the induction and maintenance of various pain conditions were activated by the ERK1/2 MAPK pathway. [2930] Recent work showed that the voltage-gated sodium channels, such as Nav1.3 and Nav1.8, can been regulated by MAPK pathway in DRG neurons and the voltage-gated sodium channels play important role in neuralgia. [3132] Consequently, we believe the migraine may be caused by cytokines, such as IL-6 and IL-1β which induced by CGRP.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the serum IL-6 level is significantly increased. The increased IL-6 can stimulate the proliferation of mesangial cells, induce the pathological changes of glomeruli and abnormal structure and function 22 . In addition, IL-6 can stimulate the hepatocytes to produce a large number of hs-CRP, which induces or aggravates the inflammatory response 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Under certain situation, mesangial cells also can secrete IL-6 and activate inflammatory cells which play an essential role in immune and metabolism-mediated injury of kidney ( 110 112 ). As we know, mesangial cells only express the gp130 and not the IL-6R.…”
Section: Il-6 and Immune And Inflammatory Cellsmentioning
confidence: 99%